PENGARUH VARIASI REDUKSI KETEBALAN COLD ROLLING SERTA SUHU ANNEALING TERHADAP SIFAT FISIK DAN MEKANIK ALUMINUM ALLOY 6082-T6 - Rian Cahya Putra; Indri Yaningsih; Teguh Triyono (Jurnal Teknika, 2017)
The effects of the reduction of thickness and temperature annealing on the physical properties and mechanical properties of metal AA 6082 have been investigated in this study. Pressed force, and rolling time were constantly maintained. Annealing was carried out at 415 C for 150 minute to increase formability. Cold rolling was carried out at room temperature with varying thickness. The thickness was reduced from 3 mm to 2,5 mm, 2 mm, and 1,5 mm. the cold rolled samples ware annealed at various tempers in the range of 275oC, 325C, and 375C for 5 minute. Vickers hardness test were performed to evaluate the mechanical properties of alloy and the microstructure were performed to evaluate the physical properties of alloy. The result shows that hardness in 50% (1,5 mm) whithout annealed reduction produce the highest hardness 115,56 Hv.it has been observed that that as the degree of cold rolling increase the value of hardness couse cold rolling can introduce high density of dislocations. Annealing can refine the grain size, especially the grain length, resulting lower hardness.